Root Diseases of Shisham (Dalbergia sissoo Roxb.) - Bakshi, B. K.; Singh, Sujan (Indian Forester, 1959)
The parasitism of Fusarium solani (Martius) Appel and Wollenweber forma dalbergiae Gordon, causing wilt in shisham was established by artificial inoculations with the fungus on shisham. All the symptoms of wilt observed in nature could be reproduced on inoculated trees.